Teacher’s Knowledges in Teaching Speaking through Merdeka Mengajar Platform: Challenges - Alamsyah Alamsyah; Isti Siti Saleha Gandana (English Education Journal, 2023)
Teacher’s knowledge has an important role in successing the teaching and learning process in the classroom. In getting knowledge, teacher can use an online platform as Merdeka Mengajar platform. It is a can be used as a source in getting knowledge in teaching speaking. This study aims to examine English teachers’ challenges in applying knowledge (in teaching speaking) obtained through the use of the Merdeka Mengajar platform. The research employed a qualitative method with a case study as a design. The participant was one English teacher at a public junior high school in Bombana Regency. The instrument used semi-structured interviews to collect data. The findings found three kinds of teacher challenges namely: (1) linguistic factors including students’ lack of English vocabulary, difficulties in memorizing vocabulary and material, incorrect pronunciation of vocabulary, (2) physiological factors contain students’ lack of confidence and motivation in speaking English), and (3) external factors such as the lack of learning support facilities in teaching speaking especially projectors and limited time in applying student-centered method. So, this research concluded that the teacher was still facing the challenges in applying knowledge obtained through MPP when teaching speaking in the clasroom This research has several positive impacts namely; introduction to the Merdeka Mengajar Platform, identify teacher challenges, and further understanding of the challenges of teaching speaking.